Inhibition of Mammary Gland Cancer Development by Propolis and Mangostin in Female Mice Balb/C - Marselina Irasonia Tan; Irham Hayati (Institute for Research and Community Services (LPPM) ITB, 2017)
The development of breast cancer involves many processes, including angiogenesis and metastasis. Some factors play a major role in angiogenesis, such as HIF-1Î±, and in metastasis, such as FAK and Wnt2. The aim of this study was to observe the effect of propolis and mangostin on the development of mammary gland cancer and on the expression of Wnt2 and FAK in Balb/C mice. Mammary gland tumors were induced in Balb/C mice by DMBA. The mice were divided into 5 treatment groups: negative control (K